Volume 1: Turbomachinery 1995
DOI: 10.1115/95-gt-212
|View full text |Cite
|
Sign up to set email alerts
|

Simple Design Methods for the Prediction of Radial Static Pressure Distributions in a Rotor-Stator Cavity With Radial Inflow

Abstract: Research has been conducted into the effects of component geometry and air bleed flow on the radial variation of static pressure and core tangential velocity in a rotor-stator cavity of the type often found behind the impeller of a gas turbine engine centrifugal compressor. A CFD code, validated by rig test data for a wide range of rotor-stator axial gaps and throughflows, has been used to generate pressure and velocity data for typical gas turbine operating conditions. This data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…It is found that the value of β 0 has a significant influence on the distribution of the swirl ratio β in the central core region. Hart and Turner [9,10] used numerical and experimental methods to obtain the pressure and swirl ratio in the impeller rear cavities with different geometries and air bleed flow. The aim of their researches was to obtain a series of curves that can help predict velocity and pressure distribution quickly and accurately without the need for costly CFD work or rig testing during the initial engine design phase.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the value of β 0 has a significant influence on the distribution of the swirl ratio β in the central core region. Hart and Turner [9,10] used numerical and experimental methods to obtain the pressure and swirl ratio in the impeller rear cavities with different geometries and air bleed flow. The aim of their researches was to obtain a series of curves that can help predict velocity and pressure distribution quickly and accurately without the need for costly CFD work or rig testing during the initial engine design phase.…”
Section: Introductionmentioning
confidence: 99%